From risky individuals to risky systems: a conceptual framework for the next generation of forensic mental health research - Crocker, Anne G.; Leclair, Marichelle (Frontiers in Psychiatry, 2025)
Risk in forensic mental health is often shaped as an individual issue. But what if risk is also produced by the systems meant to provide care and safety? This paper introduces the Risk in Systems Framework, a conceptual model to understand how risk emerges not just within people, but also through institutional practices and structural inequalities. Drawing on established models from criminology, psychology, and public health, the framework explores risk across three levels: the individual, the system, and the broader social structures. It helps identify how policies, professional norms, and historical legacies can shape who is labelled risky and what responses are considered appropriate. By shifting the focus from “risky individuals” to “risky systems,” this approach supports more responsive care for people in forensic mental health settings.